2016
DOI: 10.1016/j.ijscr.2016.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine Porocarcinoma presenting as an abdominal wall mass in a patient with ulcerative colitis—A rare case report

Abstract: HighlightsEccrine Porocarcinoma (EPC) is rare. It seldom occurs in the early 20s, or arises in the abdominal wallEPC is easily misdiagnosed due to lack of specific morphological features. Clinical picture usually consists of a painless nodule or papuleDefinitive diagnosis is achieved by histopathological examinationEarly definitive surgical excision with wide tumor free margins leads excellent results. Risk of local recurrence is about 20%High index of suspicion for EPC should be maintained in patients with cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These includes; ductal differentiation, nests of basaloid cells, squamoid tumor cells, infiltrative spinal cells, cells of acanthotic epidermis, Borst Judasson appearance, ulcerated epithelial tumor, bowenoid porocarcinoma, nests of small atypical cells, clear-cell, high infilterative pattern and hyperchromatic nuclear [7] , [13] , [26] , [62] , [72] , [103] , [102] . Surgery was the main mode of therapy with adjuvant chemoradiotherapy if metastasis and/or recurrence occurred [50] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] . Metastasis was found in 110 (31%) cases [3] , [10] , [63] , [65] , [68] , [73] , [76] , [86] .…”
Section: Discussionmentioning
confidence: 99%
“…These includes; ductal differentiation, nests of basaloid cells, squamoid tumor cells, infiltrative spinal cells, cells of acanthotic epidermis, Borst Judasson appearance, ulcerated epithelial tumor, bowenoid porocarcinoma, nests of small atypical cells, clear-cell, high infilterative pattern and hyperchromatic nuclear [7] , [13] , [26] , [62] , [72] , [103] , [102] . Surgery was the main mode of therapy with adjuvant chemoradiotherapy if metastasis and/or recurrence occurred [50] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] . Metastasis was found in 110 (31%) cases [3] , [10] , [63] , [65] , [68] , [73] , [76] , [86] .…”
Section: Discussionmentioning
confidence: 99%
“…[2], [3], [13], [11], [16], [17], [19], [23], [25], [27], [28], [31], [32] EP occurs as a single mass or nodule in 72% of the cases, ulceration (26%), and as a discharging sinus in 2% of cases. [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36] Although the pre-invasive markers and the pathogenesis of EP are not clear, according to some papers, risk factors include exposure of the affected area to trauma, burning, or radiotherapy, immunosuppressive drugs especially after organ transplantation, prolonged exposure to ultraviolet light and AIDS. [10] The gross examination is an important part of the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[3], [4] Patient age varies according to different studies, ranging from 21 to 90. [5], [6] It predominantly occurs in elderly people who are more than 60 years old and has a female predominance. [4]…”
Section: Introductionmentioning
confidence: 99%
“…(Robson et al, 2001) Because of synchronous epidermoid differentiation, diagnosis of EPC can be further supported by immunohistochemical staining for carcinoembryonic antigen (CEA), epithelial membrane antigen (EMA), and p53. (Robson et al, 2001;Parmar et al, 2016;Akalin et al, 2001) Positive staining for CEA and/or EMA usually accentuates ductal differentiation. (Robson et al, 2001;Parmar et al, 2016) Our case also showed infiltrative margins and positive CEA staining.…”
Section: Discussionmentioning
confidence: 99%
“…(Robson et al, 2001;Parmar et al, 2016;Akalin et al, 2001) Positive staining for CEA and/or EMA usually accentuates ductal differentiation. (Robson et al, 2001;Parmar et al, 2016) Our case also showed infiltrative margins and positive CEA staining.…”
Section: Discussionmentioning
confidence: 99%